Miasma e condizione eroica nell’Iliade - Sforza, Ilaria (O T I V M, 2017)
In this paper, we conduct an analysis of the Homeric occurrences of the word κόνισ, «dust, ashes», starting from the passage in which Achilles‟ horses mourning Patroclus refuse to move (Il. 17, 426-440). Their manes trailing in the dust recall significantly Achilles‟ reaction when Antilochus told him of Patroclus‟ death (Il. 18, 22-27). Similarly, in the Epic of Gilgamesh, the hero reacts to the death of his dear friend Enkidu (tab. VIII 56-63). But Gilgamesh‟s fear of death begins after his facing with the decomposition of Enkidu‟s corpse (tab. X 60-75). In the Iliad, hero‟s death begins when his head or his hair comes in contact with dust. Nevertheless, some heroes, like Hector and Sarpedon, are exceptionally preserved by the divine injection of nectar and ambrosia. This divine action could be interpreted as an attempt to preserve, together with the charis, also the memory of the hero unchanged in time.